THEORY OF INTERNATIONAL RELATIONS IN THE MIRROR OF CONTEMPORARY RUSSIAN INTERNATIONAL STUDIES - M. M. Lebedeva; M. V. Harkevich (Vestnik MGIMO-Universiteta, 2016)
The article deals with the evolution of Western theories of international relations in the postSoviet Russia, it analyzes the world view of Russian international scholars, as well as their reflection on the epistemological foundations of the probable Russian IR school. It states that pluralization of theoretical approaches continues in Russia, while liberalism is gradually givingup to realism on the way to the dominant theory. Constructivism is gaining popularity and postmodernism remains without followers. Russian international studies are structured by a long-standing debate about the identity of Russia. "Westerners" continue to argue with "Slavophiles."Sometimes these arguments translate into a cry for building independent national school of international relations, thereby exacerbating the problem of epistemological relativism. The bases for the school may be found in Russian spiritual philosophy, the Tartu-Moscow school of semiotics, Russian cultural studies, postcolonial tradition of national historical science.